2018
DOI: 10.1017/gmh.2018.7
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a common elements treatment approach for youth in Somali refugee camps

Abstract: Background.This paper reports on: (1) an evaluation of a common elements treatment approach (CETA) developed for comorbid presentations of depression, anxiety, traumatic stress, and/or externalizing symptoms among children in three Somali refugee camps on the Ethiopian/Somali border, and (2) an evaluation of implementation factors from the perspective of staff, lay providers, and families who engaged in the intervention.Methods.This project was conducted in three refugee camps and utilized locally validated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 64 publications
3
78
0
Order By: Relevance
“…CETA has been described elsewhere in greater detail (https://www.cetaglobal.org) [24]. CETA has also shown effectiveness in reducing internalizing symptoms, externalizing behaviors, and posttraumatic stress, and improving well-being, among Somali refugee youth in Ethiopia in an open trial [32].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CETA has been described elsewhere in greater detail (https://www.cetaglobal.org) [24]. CETA has also shown effectiveness in reducing internalizing symptoms, externalizing behaviors, and posttraumatic stress, and improving well-being, among Somali refugee youth in Ethiopia in an open trial [32].…”
Section: Methodsmentioning
confidence: 99%
“…Currently, CETA is the only modular, flexible, multi-problem, transdiagnostic approach delivered by lay providers that has multiple RCT evaluations in LMICs. Adding to the existing evidence showing CETA's effectiveness on a range of mental and behavioral health issues [30][31][32], this trial provides evidence of the broader effectiveness of CETA in addressing social issues of IPV and alcohol misuse. Collectively, the evidence suggests that this transdiagnostic model can more effectively, efficiently, and economically address naturally occurring comorbidity in the human population to reduce the mental and behavioral health treatment gap in LMICs than interventions that focus on a single problem.…”
Section: Plos Medicinementioning
confidence: 99%
“…These findings provide some evidence of effectiveness for CETA with adults, as well as ability of lay providers to learn this type of modular, flexible approach. In Ethiopia, results showed significant decreases in symptoms of internalizing ( d = 1.37), externalizing ( d = 0.85), and post-traumatic stress ( d = 1.71) symptoms, and improvements in well-being ( d = 0.75) (Murray et al under review ). The modular nature of CETA allowed us to develop and adapt the elements and flows to fit our study population.…”
Section: Methodsmentioning
confidence: 99%
“…Results from these studies have been used for design of modular and element-based interventions tailored to individual needs (e.g., Murray et al 2018), empirical testing of singular elements (e.g., Leijten et al 2015), and to inform training and consultation in children's mental health services (e.g., Dorsey et al 2016). To our knowledge, no prior study has systematically identified the common elements of effective OSTA interventions for children at risk.…”
Section: Introductionmentioning
confidence: 99%